Conclusion [in Boosting growth to end hunger by 2025: The role of social protection] - Wouterse, Fleur Stephanie; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
Chapter 13 provides an overarching account of findings on social protection as development policy and draws out lessons for policy makers when adopting a systems approach to social protection.